Valorização da ß-glucana como imunoestimulante para uso em dietas e vacinas - Domenico, Janine Di (2015)
In this work we evaluated the effect of β-glucan on silver catfish (Rhamdia quelen) innate and acquired immune response. In the first experiment, bovine serum albumin (BSA; 200 μg/fish) was mixed to β-glucan (0,02%, 0,06% e 0,1%) or montanide and inoculated intraperitoneally. Blood samples were collected prior to or at 14, 28 and 42 days post inoculation (dpi) to estimate the production of anti-BSA antibodies. In the second experiment, β-glucan was added to the diet (0,01% and 0,1%) and fed to the fish for 21 days to evaluate blood cells and innate immune parameters, or 42 days, to evaluate specific growth rate (SGR) and survival to challenge with Aeromonas hydrophila. Silver catfish immunized with BSA+β-glucan (0,02% and 0,06%) had higher (p < 0.05) anti-BSA antibodies at 28 and 42 dpi compared to the fish inoculated with BSA alone, but at similar levels than fish inoculated with BSA+Montanide. Blood cell counting on fish fed β-glucan for 21 days indicated a small, non-significant decrease in the number of most cells after the feeding trial, suggesting that fish confinement in tanks might have contributed to reduce the overall blood cell counting. However, in fish fed β-glucan the natural hemolytic activity of complement was significantly higher (p<0.05) compared to control fish. Feeding fish for 42 days with β-glucan had no effect on SGR. However, after challenging with intraperitoneal inoculation of A. hydrophila, the amount of bacteria isolated from blood was significantly lower (p<0.05) and the daily survival rate was significantly higher (p<0.05) in fish that received β-glucan in the diet compared to the control fish. Taken together, our results indicate that β-glucan might be exploited as vaccine adjuvant and feeding fish with β-glucan has a beneficial effect on innate immune system and contributes to improve resistance to infection by A. hydrophila